REPRESENTASI SIMBOLISME KASIH SAYANG DALAM FILM BILA ESOK IBU TIADA (ANALISIS SEMIOTIK) - Kartika, Rika; Kusyani, Diah (LUMBUNG AKSARA, 2024)
This study focuses on the analysis of the film "Bila Esok Ibu Tiada" using a semiotic approach to explore the representation of a mother's affection for her child. Qualitative descriptive methods are applied to identify and interpret various semiotic signs found in the film, including interactions between characters, storylines, and visual and verbal symbols. By referring to Charles Sanders Peirce's semiotic theory, this study explores the meaning contained in these symbols, showing how the film communicates the complexity of a mother's affection and sacrifice. The results of the analysis show that the symbolism in the film not only conveys emotions, but also highlights social values ​​and deep family relationships.